The Influence of Human Resources and Infrastructure on the Performance of Military Teachers in Special Forces Training Education Centers - I Wayan Laba; Ferikawita Magdalena Sembiring (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
The research, entitled "The Impact of Human Resources and Infrastructure on the Performance of Military Instructors at the Special Forces Training Education Centre (Pusdiklatpassus)", analyses the effect of human resources and infrastructure on the performance of military instructors. The research challenge is to identify the impact of these factors on troops who perform poorly. The objective is to determine the extent to which human resources and infrastructure influence the effectiveness of military instructors. The objective of this study is to describe and analyse the impact of human resources, infrastructure, and military instructor performance at the Special Forces Training Education Centre (Pusdiklatpassus). The research employs a quantitative explanatory survey methodology. A literature study and questionnaire-based field research were used to obtain data. AMOS 22.0 software is used for structural equation modelling (SEM). A sample of 71 was drawn from an 87-person population using basic random sampling. The investigation found that the Human Resources and Infrastructure variable scored 54.44%, which is satisfactory. The military instructors' 57.84% score is moderate. The hypothesis test for the impact of Human Resources and Infrastructure on Military Teacher Performance indicated a positive estimate of 3.509 (73%), with a p-value of 0.018 (<0.05). Consequently, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) accepted, thereby indicating that Human Resources and Infrastructure affect Military Teacher Performance.